Fixed or adjustable sling in the treatment of male stress urinary incontinence: results from a large cohort study - Hüsch, Tanja; Kretschmer, Alexander; Obaje, Alice; Kirschner-Hermanns, Ruth; Anding, Ralf; Pottek, Tobias; Rose, Achim; Olianas, Roberto; Friedl, Alexander; Homberg, Roland; Pfitzenmaier, Jesco; Abdunnur, Rudi; et al. (Translational andrology and urology, 2020)
Background: Fixed and adjustable male slings for the treatment of male urinary stress incontinence became increasingly popular during the last decade. Although fixed slings are recommended for the treatment of mild to moderate stress urinary incontinence, there is still a lack of evidence regarding the precise indication for an adjustable male sling. Furthermore, there is still no evidence that one type of male sling is superior to another. However, both, adjustable and fixed slings, are commonly utilized in daily clinical practice. This current investigation aims to evaluate the differences between fixed and adjustable male slings regarding indications, complication rates and functional outcome in the treatment of male stress urinary incontinence in current clinical practice. Methods: A total of 294 patients with a fixed and 176 patients with an adjustable male sling were evaluated in a multicenter single arm cohort trial. Data collection was performed retrospectively according the medical record. Functional outcome was prospectively analyzed by standardized, validated questionnaires. Descriptive statistics was performed to present patient characteristics, complication rates and functional outcome. A chi2-test for categorical and independent t-test for continuous variables was performed to identify heterogeneity between the groups and to correlate preoperative characteristics with the outcome. A P value <0.05 was considered statistically significant. Results: Patients with higher degree of urinary incontinence (P<0.001) and risk factors such as history of pelvic irradiation (P<0.001) or prior surgery for urethral stricture (P=0.032) were more likely to receive an adjustable MS. Complication rates were comparable except for infection (P=0.009, 0 vs. 2.3%) and pain (P=0.001, 1.7% vs. 11.3%) which occurred more frequently in adjustable slings. Functional outcome according validated questionnaires demonstrated no differences between fixed and adjustable male slings. Conclusions: Adjustable male slings are more frequently utilized in patients with higher degree of incontinence and risk factors compared to fixed slings. No differences could be identified between functional outcome which may imply an advantage for adjustability. However, pain and infection rates were significantly higher in adjustable MS and should be considered in the decision process for sling type.
Gesehen am 17.09.2020